2021
DOI: 10.3390/su13074012
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Air Quality on Effective Labor Supply: Based on the Survey Data of Zhejiang Province in China

Abstract: Labor is one of the most important factors of production and the basis for the development of social productivity. China’s aging population problem is serious, and the study of the labor supply is of great importance in order to achieve its second centenary goal regarding social development. In this study, four stage mixed sampling was used to conduct a questionnaire survey in the Zhejiang province of China, and 590 valid questionnaires were obtained. An ordered logit model and sample selection model were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
(78 reference statements)
0
1
0
Order By: Relevance
“…The OLS regression results demonstrate that age has a substantial positive impact on the PEB of rural people among the control variables, implying that the older the residents are, the more active they are in PEB. The selection of control variables in this paper is similar to that of Yang et al [70]. Yin et al demonstrated that public environmental concerns have no significant impact on their environmental engagement [60], considering gender, age, and income levels as control variables.…”
Section: Benchmark Regressionmentioning
confidence: 89%
“…The OLS regression results demonstrate that age has a substantial positive impact on the PEB of rural people among the control variables, implying that the older the residents are, the more active they are in PEB. The selection of control variables in this paper is similar to that of Yang et al [70]. Yin et al demonstrated that public environmental concerns have no significant impact on their environmental engagement [60], considering gender, age, and income levels as control variables.…”
Section: Benchmark Regressionmentioning
confidence: 89%